Effects of exogenous, nonleukemogenic, ecotropic murine leukemia virus infections on the immune systems of adult C57BL/6 mice. - Lee, J S (1995)
Mouse AIDS (MAIDS) develops in mice infected with a mixture of replication-competent ecotropic and mink lung cell focus-inducing murine leukemia viruses and an etiologic replication-defective virus. Helper viruses are not required for induction of MAIDS, but the time course of disease is accelerated in their presence. To understand the possible contributions of ectropic murine leukemia viruses to MAIDS pathogenesis, we biologically cloned a series of viruses from the MAIDS-inducing LP-BM5 virus mixture. These viruses were examined for replication in tissues of infected mice and for effects on the immune system. All virus stocks replicated efficiently in mice. Infected animals showed slight lymphadenopathy and splenomegaly due primarily to B-cell proliferation associated with differentiation to immunoglobulin secretion resulting in twofold increases in serum immunoglobulin M levels; however, B-cell responses to helper T-cell-independent antigens were increased rather than decreased as in MAIDS. Analyses of CD8+ T-cell function showed that cytotoxic T-lymphocyte responses to alloantigens were comparable in control and infected mice. Finally, we showed that infection resulted in enhanced expression of transcripts for interleukin-10, interleukin-4, and gamma interferon. These cytokines can all contribute to B-cell activation and may promote the expansion of a target cell population for the MAIDS defective virus.